Kontes Ternak sebagai strategi peningkatan minat peternak OAP terhadap sapi Bali: Livestock contest as a strategy to increase Indigenous Papuan farmers’ interest in Bali cattle - Sumpe, Iriani; Seseray , Daniel Y.; Widayati , Trisiwi W.; Tethool , Angelina; Sawen, Diana; Monim , Hanike; Lekitoo , Merlyn N.; Palulungan, John A.; Wajo , Mohamad Jen; Haryati, Stefani F.; Rahayu, Bernadetta W. I. (IGKOJEI: Jurnal Pengabdian Masyarakat, 2025)
ABSTRACT  A livestock contest is a strategic approach that can encourage improvements in maintenance quality and motivate farmers in developing their livestock. This activity was carried out in Sorong Regency, Southwest Papua, involving 30 Indigenous Papuan (OAP) farmers with a total of 50 Bali cattle. After administrative selection and health checks, 34 cattle were assessed based on morphometric parameters, Body Condition Score (BCS), estimated body weight, and maintenance management. The results showed significant variation in livestock performance and the level of adoption of maintenance practices. Farmers’ involvement in the measurement process provided direct educational experiences and increased awareness of the importance of data-based management and livestock breeding selection to improve productivity. In addition to identifying livestock individuals with superior genetic potential, the contest also encouraged a shift in farmers’ mindset toward sustainable livestock development. This model is recommended as a replicable approach for regions with similar socio-economic conditions.  Keywords: Bali cattle; husbandry management; Indigenous Papuan; livestock contest; selective breeding   ABSTRAK  Kontes ternak merupakan pendekatan strategis yang dapat mendorong peningkatan kualitas pemeliharaan dan motivasi peternak dalam mengembangkan ternaknya. Kegiatan ini dilaksanakan di Kabupaten Sorong, Papua Barat Daya, melibatkan 30 peternak Orang Asli Papua (OAP) dengan total 50 ekor sapi Bali. Setelah seleksi administratif dan pemeriksaan kesehatan, 34 ekor sapi dinilai berdasarkan parameter morfometrik, Body Condition Score (BCS), estimasi bobot badan, dan manajemen pemeliharaan. Hasil menunjukkan variasi signifikan dalam performa ternak dan tingkat adopsi praktik pemeliharaan. Keterlibatan peternak dalam proses pengukuran menciptakan pengalaman edukatif langsung dan meningkatkan kesadaran akan pentingnya manajemen -pemeliharaan dan seleksi bibit ternak untuk meningkatkan produktivitas ternak. Selain mengidentifikasi individu ternak berpotensi genetik unggul, kontes ini juga mendorong perubahan pola pikir peternak ke arah pengembangan ternak berkelanjutan. Model ini direkomendasikan sebagai pendekatan replikatif untuk wilayah dengan kondisi sosial-ekonomi serupa. Kata kunci: kontes ternak; manajemen pemeliharaan; Orang Asli Papua; pemuliaan selektif; sapi Bali